Performance Evaluation of Inclined-Step and Wall Roughness on Battery Thermal Management System - Olanrewaju M. Oyewola; Emmanuel T. Idowu; Morakinyo J. Labiran; Michael C. Hatfield; Mebougna L. Drabo (Emerging Science Journal, 2026)
In this study, the effects of inclined steps and wall roughness on the step-like plenum of the Z-type battery thermal management system (BTMS) are examined, extending the literature on its design. Due to the performance of the design in achieving a reduction in maximum temperature (Tmax), additional modifications are required to provide more insight into further enhancing the thermal performance and overcoming the design’s drawback, such as higher pressure drop (ΔP). The performance of the system was evaluated in terms of the  and maximum temperature difference (ΔTmax) of batteries in the systems and ΔP across the system. The temperature values were selected after comparing the maximum temperatures recorded on each battery.  Investigations were carried out using a Computational Fluid Dynamics (CFD) method, which was validated by comparing with experimental data from the literature. Findings revealed that the step designs with inclined angles of 5°, 45° and 85° reduced the Tmax by 3.18 K, 3.9 K, and 4.34 K, respectively, when compared to the Z-type design. However, the Z-type design has the lowest ΔP value (16.50 Pa), while the original step-like design system produced the highest value (20.96 Pa). When considering the roughness, by increasing the roughness height from 5 μm to 10 μm, an increase in Tmax was observed, while wall roughness generally decreases the ΔP. From 0 to 10 μm, Tmax increased by 0.03 K (0.01%) and ΔP increased by 0.07 Pa (0.29 %), indicating negligible effects. The study, therefore, concludes that adequate selection of step design with different angles, air inlet velocity, temperature, and wall roughness will be highly beneficial for designing cost-effective and efficient BTMSs.